The Relationship between Creative Thinking, Problem Solving Skills, and Self Efficacy with Work Readiness - Nihlatin Nisa, Alis; Puji Sugiharto, Dwi Yuwono; Awalya, Awalya (Universitas Negeri Semarang, 2021)
Student’s work readiness is related to individual abilities such as creative thinking, problem solving skills, and self-efficacy. However, the readiness is sometimes not matched by the expected requirements from industrial world. Hence, this study strived to analyze the relationship between creative thinking, problem solving skills, and self-efficacy with the work readiness of Public Vocational High School students in Semarang City. Regarding sample, this study involved 372 students in 6 Public Vocational High School in Semarang City chosen using Cluster Random Sampling. The sample data were collected through the instruments of creative thinking scale, Problem Solving Inventory (PSI), General Self-Efficacy (GSE), and work readiness scale. The findings showed that; creative thinking, problem solving skills and self-efficacy had positive relationships with work readiness. In details, self-efficacy variable owned the strongest relationship among other variables. Thus, the higher the creative thinking, problem solving skills, and self-efficacy students have, the higher work readiness in facing the industrial world and the world of work would be.